Potential Diagnostic Hemorheological Indexes for Chronic Kidney Disease in Patients With Type 2 Diabetes - Lee, Hoyoon; Na, Wonwhi; Lee, Sang Bae; Ahn, Chul Woo; Moon, Jun Sung; Won, Kyu Chang; Shin, Sehyun (Frontiers in Physiology, 2019)
Many studies have demonstrated that an alteration in hemorheological properties, such as red blood cell (RBC) deformability, is closely correlated with diabetic microcirculatory diseases. However, most of these studies have been limited to animal studies or used a small number of clinical samples, due to a lack of effective point-of-care (POC) devices to measure such properties within clinical environments. Owing to recent developments in microfluidic technology, several hemorheological POC devices have been designed that allow for the possibility of conducting extensive clinical studies using hemorheological measurements. Here, we reviewed recent clinical studies of chronic kidney disease and diabetic nephropathy in patients with type 2 diabetes associated with hemorheological parameters. We found that RBC deformability alone did not show a significant difference according to the degree of DN, whereas critical shear stress was closely correlated with the glomerular filtration ratio and the albumin-to-creatinine ratio. We also reviewed studies that alteration of hemorheological properties are associated with the development of DN, which showed that critical shear stress could be considered as a potential index to diagnose not only diabetes-related kidney disease but also other diabetes-related complications.